Fear conditioning and extinction distinctively alter bidirectional synaptic plasticity within the amygdala of an animal model of post-traumatic stress disorder - Kwanghoon Park; Hoyong Park; ChiHye Chung (Neurobiology of Stress, 2024)
Synaptic plasticity in the amygdala plays an essential role in the formation and inhibition of fear memory; however, this plasticity has mainly been studied in the lateral amygdala, making it largely uninvestigated in other subnuclei. Here, we investigated long-term potentiation (LTP) and long-term depression (LTD) in the basolateral amygdala (BLA) to the medial division of the central amygdala (CEm) synapses of juvenile C57BL/6N (B6) and 129S1/SvImJ (S1) mice. We found that in naïve B6 and S1 mice, LTP was not induced at the BLA to CEm synapses, whereas fear conditioning lowered the threshold for LTP induction in these synapses of both B6 and S1 mice. Interestingly, fear extinction disrupted the induction of LTP at the BLA to CEm synapses of B6 mice, whereas LTP was left intact in S1 mice. Both low-frequency stimulation (LFS) and modest LFS (mLFS) induced LTD in naïve B6 and S1 mice, suggesting that the BLA to CEm synapses express bidirectional plasticity. Fear conditioning disrupted both types of LTD induction selectively in S1 mice and LFS-LTD, presumably NMDAR-dependent LTD was partially recovered by fear extinction. However, mLFS-LTD which has been known to be endocannabinoid receptor 1 (CB1R)-dependent was not induced after fear extinction in both mouse strains. Our observations suggest that fear conditioning enhances LTP while fear extinction diminishes LTP at the BLA to the CEm synapses of B6 mice with successful extinction. Considering that S1 mice showed strong fear conditioning and impaired extinction, strong fear conditioning in the S1 strain may be related to disrupted LTD, and impaired extinction may be due to constant LTP and weak LFS-LTD at the BLA to CEm synapses. Our study contributes to the further understanding of the dynamics of synaptic potentiation and depression between the subnuclei of the amygdala in juvenile mice after fear conditioning and extinction.